Superficial anorectal abscess resembling a lipoma: A case report. Issue 12 (2nd August 2020) - Kogo, Hideki; Takasaki, Hideaki; Sakata, Yoshinori; Nakamura, Yoshiharu; Yoshida, Hiroshi
Abstract: Perianal abscesses exist in various forms depending on the location. Clinical examination and endorectal ultrasound (EUS) may be useful for the diagnosis of anal tumor. Abstract : Perianal abscesses exist in various forms depending on the location. Clinical examination and endorectal ultrasound (EUS) may be useful for the diagnosis of anal tumor.